2014
DOI: 10.1186/1471-2172-15-24
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiotic Lactobacillus jensenii as immune-health promoting factor to improve growth performance and productivity in post-weaning pigs

Abstract: BackgroundImmunoregulatory probiotics (immunobiotics) have been proposed to improve piglets’ immune system to avoid intestinal infections and reduce unproductive inflammation after weaning. Previously, it was demonstrated that Lactobacillus jensenii TL2937 (LjTL2937) attenuated the inflammatory response triggered by activation of Toll-like receptor 4 (TLR-4) in porcine intestinal epithelial (PIE) cells and antigen presenting cells (APCs) from porcine Peyer’s patches (PP).ObjectiveIn view of the critical import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 31 publications
6
63
0
1
Order By: Relevance
“…, ) and regulation of the immune system (Suda et al . ). All of these traits impact the gut microbial populations such that opportunistic pathogens including Salmonella , Clostridia and Enterobacteria are kept in check, thus preventing infection and intestinal disorders (Nemcova et al .…”
Section: The Role Of Lactobacilli In Swine Husbandrymentioning
confidence: 97%
See 1 more Smart Citation
“…, ) and regulation of the immune system (Suda et al . ). All of these traits impact the gut microbial populations such that opportunistic pathogens including Salmonella , Clostridia and Enterobacteria are kept in check, thus preventing infection and intestinal disorders (Nemcova et al .…”
Section: The Role Of Lactobacilli In Swine Husbandrymentioning
confidence: 97%
“…An in‐depth analysis of the immune health promoting properties of L. jensenii TL2937 demonstrated that the use of immunobiotic strains as supplemental additives to piglets’ feed significantly reduced tenderness and improved juiciness and palatability of pork meat, along with reducing backfat thickness (Suda et al . ). In addition, Ross et al .…”
Section: The Role Of Lactobacilli In Swine Husbandrymentioning
confidence: 97%
“…Probiotics contribute to maintaining a healthy digestive system of the host via regulating both intestinal development and flora balance [13], some of which have been shown to enhance the host immune responses by regulating cytokine and chemokine production [2]. L. acidophilus strain is a well-characterized probiotic bacterium, which has been reported to improve the production performance of animals as well as enhance the immune responses [46].…”
Section: Introductionmentioning
confidence: 99%
“…Es cada vez más reconocido que el epitelio intestinal está jugando un papel esencial en la homeostasis inmune, mediante la promoción de respuestas tolerogénicas y regulatorias. Estos resultados tienen implicaciones importantes sobre la regulación de la homeostasis de la mucosa por las bacterias probióticas (Suda et al, 2014), explicando la regulación de la respuesta inmune contra los probióticos. Como se observó en los resultados de esta investigación se presentó un proceso de tolerancia a favor de los probióti-cos y, por ende, una adaptación a dichos microorganismos.…”
Section: Discussionunclassified